Science teaching: science teachers in Trinidad and Tobago share their stories. Issue 1 (2nd January 2019) - Maharaj-Sharma, Rawatee; Sharma, Aarti
ABSTRACT: Qualitative narrative inquiry using exploratory interviews with five experienced secondary school science teachers in Trinidad and Tobago were analysed to reveal what learnings can be derived from the experiences and stories shared by these individuals. The stories present science teaching as an evolutionary process, which portrays science teaching with the following attributes: a work in progress, a haven for students, a lifelong vocation, and a personal commitment. Integral elements of science teaching as a process rather than a product in an atmosphere of discipline, respect, and trustworthiness were revealed. While this work is instructive for aspiring teachers and has several implications for teacher preparation programmes, the aim in this instance is to share the stories of these five teachers, and in that regard it serves a celebratory rather than a theoretical purpose.